IMPLEMENTASI KEBIJAKAN PELAYANAN UNTUK PENINGKATAN JUMLAH NASABAH (STUDY KASUS PT. PEGADAIAN (PERSERO) CABANG SIBOLGA) - Yenni Sofiana Tambunan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study is entitled "Implementation of Service Policies for Increasied the Number of Customers. The purpose of this study was to determined the effect of service policy implementation on increasing the number of customers at PT. The analytical method used is the analysis method of the correlation test, determination test, simple linear regression analysis and statistical T test. Correlation test results indicate that there is a positive relationship between service policied with an increase in the number of customers by 0.869 so that when interpreted in the value scale it can be categorized as high with the linear regression equation Y = 8.067 + 0.838 X. Hypothesis test results partically indicated that service policy is influential positively and significantly to the increasing number of customers at PT. Pegadaian (Persero) Sibolga Branch with proven t count 8.408> t table of 2.06866. The amount of influence of policy implementation on increasing the number of customers at PT. Pegadaian (Persero) Sibolga Branch is 75.5% while 25.5% is influenced by other factors not addressed in this study.